Loss of penile length following radical prostatectomy - A. E. Osadchinskii; S. V. Kotov (Андрология и генитальная хирургия, 2022)
Introduction. The majority of patients who undergo radical prostatectomy, apart from loss of sexual function, note a decrease in penis size which negatively affects their self-esteem. Penile rehabilitation is a set of measures aimed at recovery of sexual function to improve the quality of life.Objective. To analyze various options for penile rehabilitation in order to choose a method for preventing penis size reduction in patients undergoing nerve-sparing radical prostatectomy.Materials and methods. Patients who undergo radical prostatectomy (n = 83) at status flaccid and status erect were measured: length, circumference of the base, body and glans penis (mm) at different periods of penile rehabilitation. As a control, the tumescence coefficient was determined using pharmacodopplerography. All results were evaluated before, at the 6th and 12th months after radical prostatectomy.Results. Depending on the type of restoration of erectile function, the patients were divided into several groups: group 1 – men without penile rehabilitation; group 2 – patients treated with phosphodiesterase inhibitors of type 5; group 3 – using vacuum erection device (VED) and group 4 – taking combined penile rehabilitation. Medians of tumescence coefficient in group 1 on the 6th and 12th months was 2.7 (2.4; 3.1) and 2.6 (1.9; 2.9), in group 2 – 2.8 (2.2; 3.5) and 2.9 (2.2; 3.5), in group 3 – 2.7 (2.3; 3.3) and 2.8 (2.3; 3.3), in group 4 – 3.0 (2.2; 3.2) and 3.1 (2.1; 3.2), respectively (p <0.05).Conclusion. The determination of the tumescence coefficient in dynamics showed more significant results throughout the entire observation period. Combined penile rehabilitation is an effective method of restoring erectile function and also allows to maintain the size of the penis at all follow-up periods.